Magnetic stimulation of the upper trapezius muscles in patients with migraine – A pilot study. (November 2016) - Sollmann, Nico; Trepte-Freisleder, Florian; Albers, Lucia; Jung, Nikolai H.; Mall, Volker; Meyer, Bernhard; Heinen, Florian; Krieg, Sandro M.; Landgraf, Mirjam N.
Abstract: Background: Repetitive peripheral magnetic stimulation (rPMS) has been applied to musculoskeletal pain conditions. Since recent data show that migraine and tension-type headache (TTH) might be closely related to peripheral muscular pain in the neck and shoulder region (supporting the concept of the trigemino-cervical complex (TCC)), this pilot study explores the acceptance of rPMS to the upper trapezius muscles in migraine (partly in combination with TTH). Methods: We used rPMS to stimulate active myofascial trigger points (aTrPs) of the upper trapezius muscles in 20 young adults suffering from migraine. Acceptance was assessed by a standardized questionnaire, whereas self-rated effectiveness was evaluated by headache calendars and the Migraine Disability Assessment (MIDAS). Algometry was performed to explore the local effect of rPMS on the muscles. Results: Acceptance of rPMS was shown in all subjects without any adverse events, and rPMS had a statistically significant impact on almost every parameter of the headache calendar and MIDAS. Among others, the number of migraine attacks ( p  < 0.001) and migraine intensity ( p  = 0.001) significantly decreased regarding pre- and post-stimulation assessments. Accordingly, 100.0% of subjects would repeat the stimulation, while 90.0% would recommend rPMS as a treatment option for migraine. Conclusions: rPMS might represent a promising tool to alleviate migraine symptoms within the context of myofascial pain. This might be due to stimulation-dependent modulation of the peripheral sensory effect within the TCC in migraine. However, sham-controlled studies with larger and more homogeneous cohorts are needed to prove a potential beneficial effect. Ethics Committee Registration Numbers : 356-14 and 447/14 Highlights: rPMS to the upper trapezius muscle is well-tolerated in young adults with migraine. rPMS may lead to a significant reduction in migraine frequency and intensity. rPMS may modulate the sensory effect within the trigemino-cervical complex. 90% of volunteers would recommend rPMS as a treatment option for migraine.